Sources of right to freedom of peaceful assembly - М. А. Sambor (Law and Safety)
The right to freedom of peaceful assembly is marked by the multifaceted nature of this right for society, the state, groups of individuals and individuals. The right to freedom of peaceful assembly is a manifestation of human nature in communication with other people, society and the state. The unconditional right to freedom of peaceful assembly has a rich history of its formation and development. However, without historical origins it is impossible to form an objective and necessary for the modern man to understand the content of the right to freedom of peaceful assembly.